Removal of pharmaceuticals from wastewater: A review of adsorptive approaches, modelling and mechanisms for metformin and macrolides. Issue 4 (August 2022) - Shearer, Lisa; Pap, Sabolc; Gibb, Stuart W.
Abstract: The usage of pharmaceuticals (PhCs) as an integral part of human healthcare is growing globally. However, as most current wastewater treatment plants (WWTPs) are not designed for the removal of PhC residues, effective and cost-efficient new technologies are required to meet this challenge. Adsorption has proven to be an efficient method, however, traditional adsorbents e.g., activated carbons and ion-exchange resins are often excessively costly. Therefore, there is a growing interest in novel low-cost adsorbents, which have a high affinity toward PhCs. This review focussed on two priority pharmaceutical classes, metformin (MF) a biguanide, and macrolides (e.g., clarithromycin, erythromycin, azithromycin) and assesses isotherm, kinetic and thermodynamic studies (and modelling), as well as the adsorption mechanisms with discussion on some identified mistakes and inconsistencies. The review also sought to identify gaps in knowledge that should be priorities for future investigations. The review indicated maximum adsorption capacities from Langmuir isotherm were found to be 0.34–278 mg/g for MF and 7.56–340 mg/g for macrolides. Data showed kinetics to be well represented by the pseudo-second order model and that mass transfer was predominantly controlled by both film and intraparticle diffusion. However, there was little information in the literature on the mechanisms involved in adsorption of these compounds, or involving dynamic conditions or real-world application (real effluents in environmentally relevant concentrations). Therefore, future priorities should include scale-up, effluent studies, and cost-analysis and environmental impact (e.g., Life Cycle Analysis). These are required to assess the commercial viability of the adsorbents for PhCs removal in WWTP applications. Graphical Abstract: ga1 Highlights: A review of metformin (biguanides) and macrolides removal from water by adsorption using various adsorbents. Major effect of pH on adsorption mechanisms. Incomplete and misinterpreted kinetic, isotherm and thermodynamic modelling. Lack of utilisation of characterisation techniques to determine the governing adsorption mechanisms. Economic and larger scale technical applicability of the process must be assessed.